CONSIDERAÇÕES SOBRE O USO DE SALVAGUARDAS DE INFORMAÇÕES DIGITAIS PARA O PROJETO DE CONSTRUÇÕES DE USO SENSÍVEL EM BIM - Miceli Junior, Giuseppe; Teixeira, André Cruz; Pellanda, Paulo César; Nascimento, Alexandre Fitzner (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The increasing adoption of Building Information Modeling (BIM) in the management of Architecture, Engineering and Construction design processes has stimulated the intensification of digital information flow among project stakeholders. However, in the case where strategic and sensitive projects are being developed, such as military constructions, and support facilities for justice and public security, leakages and security breaches of sensitive data may compromise associated commercial objectives and intellectual property. This paper aims to bring to light some considerations about the use of digital information safeguards for the project of sensitive public activities in BIM, by adapting the standard PAS 1192-5: 2015 to the Brazilian reality.